2022
DOI: 10.1038/s41598-022-06857-6
|View full text |Cite
|
Sign up to set email alerts
|

Mercury goes Solid at room temperature at nanoscale and a potential Hg waste storage

Abstract: While room temperature bulk mercury is liquid, it is solid in its nano-configuration (Ønano-Hg ≤ 2.5 nm). Conjugating the nano-scale size effect and the Laplace driven surface excess pressure, Hg nanoparticles of Ønano-Hg ≤ 2.4 nm embedded in a 2-D turbostratic Boron Nitride (BN) host matrix exhibited a net crystallization at room temperature via the experimentally observed (101) and (003) diffraction Bragg peaks of the solid Hg rhombohedral α-phase. The observed crystallization is correlated to a surface ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…As the size changes, in addition to the change in appearance, more complex properties such as ionic conductance [7,8], phonon signal [9], optical response [10] also changes. Kana et al [11] found that Hg nanoparticles with its size ≤ 2.4 nm exhibited a net crystallization at room temperature as it was embedded in a 2-D turbostratic boron nitride host matrix. Bonaccurso and Butt [12] studied experimentally the evaporation of water drops with radii ∼20 µm by depositing them onto atomic force microscope cantilevers, and found that during the last stage the evaporation process is slowed and a few nanometers thin layer of water remains on the surface for t ≫ 0.1 s. Similar nano-level phenomena related to the size of liquids have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As the size changes, in addition to the change in appearance, more complex properties such as ionic conductance [7,8], phonon signal [9], optical response [10] also changes. Kana et al [11] found that Hg nanoparticles with its size ≤ 2.4 nm exhibited a net crystallization at room temperature as it was embedded in a 2-D turbostratic boron nitride host matrix. Bonaccurso and Butt [12] studied experimentally the evaporation of water drops with radii ∼20 µm by depositing them onto atomic force microscope cantilevers, and found that during the last stage the evaporation process is slowed and a few nanometers thin layer of water remains on the surface for t ≫ 0.1 s. Similar nano-level phenomena related to the size of liquids have also been reported.…”
Section: Introductionmentioning
confidence: 99%